The Trade Union Movement, 1850-1914 - Antony Taylor (Revue Française de Civilisation Britannique)
This article examines the role of trade unionism in the long nineteenth century and considers the drawbacks to standard approaches to this subject. Discussing the changed focus of much historical scholarship towards the history of trade unions, it re-examines the approach to trade union history that emphasizes the movement’s affinities with the Labour party. Moving away from a focus that stresses the institutional and hierarchical histories of individual trade unions, this article explores the new directions in trade union history, stressing the movement’s links with different political parties, recent research on strike action and the rediscovery of particular strikes and the role of transnationalism and emigration in shaping the attitudes and actions of the trade union movement more broadly. Moreover, it detects a renewed focus on the material culture and historical survivals of the trade union movement, and the role of objects like banners in preserving the memory and vigour of the movement in the nineteenth century.